To study the relationship between religious coping spiritual well being, and marital adjustment, among the wives of males with Alcohol Dependence Syndrome - Chettri, G.T.; Pathak, N. (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: The impact of alcoholism on marital – family functioning and the influence of marital – family relationship on the development and the maintenance of the alcoholism are challenging problems to both the clinicians and researchers. The aim was to study the relationship between religious coping spiritual well being, and marital adjustment, among the wives of males with Alcohol Dependence Syndrome. Material And Method: Wives of alcohol dependent male patients admitted in the Department of Psychiatry, Armed Police force Hospital were included in the study after informed consent. a) Semi-Structured Proforma b) The Spiritual Well-Being Scale, C) R- COPE Scale, (D) Dyadic Adjustment Scale. were used to collect the data. Results: The results of the study show that majorities were from a rural background, low socio economic status, nuclear family and were homemakers. Spiritual well being and religious well being correlated positively with positive religious coping and inversely correlated with negative religious coping. The total score on religious coping correlated inversely with the dyadic adjustment showing that in times of stress and low marital adjustment the sample turned more to religion to help them cope. High negative correlation was seen between the dyadic adjustment of the wives and negative religious coping .The years of drinking inversely correlated with spiritual well being and the subscale of existential well being, indicating that the more number of years the patient consumed alcohol the wife had lower spiritual well being and in particular existential well being. Conclusion: Spiritual well being enhances the positive religious coping strategies of the wives of men with alcoholism in this study. When the spiritual well being is low more negative methods of religious coping are used.